The Private Sector in Water and Sanitation : How to Get Started - Brook Cowen, Penelope J. (World Bank, Washington, DC, 2012)
The more risk and responsibility a government hands over to the private sector in water and sanitation, the more powerful the incentives for better performance-but also the more demands on the government in commitment and preparation. So a government about to enter into a long partnership for a water concession or build-operate-transfer arrangement - typically for twenty-five to thirty years - needs to be sure that it does not overlook details that will later land it in messy renegotiations. A lease is less demanding, but offers smaller gains and will not fix such problems as chronic under-investment. It will, however, give the government time to prepare a longer-term option. In this Note, based on toolkits recently published by the World Bank, the author sets out the range of options for involving the private sector in water and sanitation and reviews the lessons on what can make or break a private participation process.